Concentrations of Retinol and α-Tocopherol in Tissue Samples From Anna's Hummingbirds (Calypte anna) - Diao, Stephanie M.; Poppenga, Robert H.; Gonzales Alarcio, Gwendolyne; Foley, Janet E.; Bandivadekar, Ruta R.; Aston, Linda S.; Tell, Lisa A. (Frontiers in Veterinary Science, 2020)
Retinol (vitamin A) and α-tocopherol (vitamin E) concentrations were measured in tissue samples (liver, heart, pectoral muscle, and brain) from Anna’s Hummingbirds (Calypte anna). Hummingbirds were after-hatch year birds that were sourced from various rehabilitation centers throughout California. Tissues samples were analyzed using high-performance liquid chromatography (HPLC). Minimum, maximum, mean, standard deviation (SD), and median ppm concentrations were calculated for each vitamin and tissue sample type. A novel analytical method was developed to analyze small mass tissue samples, with the smallest sample mass being 0.05 g for which analysis can be performed. Mean ± standard deviation (SD) concentrations of retinol in hummingbird livers, hearts, and pectoral muscle samples were 269.0 ± 216.9 ppm, 1.8 ± 2.2 ppm, and 0.3 ± 0.1 ppm, respectively. Mean ± SD α-tocopherol concentrations were 6.9 ± 4.6 ppm, 5.5 ± 4.0 ppm, 3.7 ± 2.2 ppm, and 9.1 ± 3.2 ppm for liver, heart, pectoral muscle, and brain samples, respectively. Vitamin concentrations from varying tissue types were compared to determine which were best associated with liver concentrations, the most commonly analyzed tissue for these vitamins. For both retinol and α-tocopherol, heart samples were most strongly associated with the liver samples. The results of this study provide baseline retinol and α-tocopherol concentrations in different tissue types from Anna’s hummingbirds. These baseline values may be utilized in conservation efforts to avoid hypervitaminosis and hypovitaminosis of rehabilitated and/or captive hummingbirds by providing guidelines for nutritional targets which could be assessed on post-mortem examinations. Post-mortem examination of birds and measurement of vitamin concentrations in tissues may allow for dietary changes that aid captive hummingbirds.